Overriding and over-extended?: actual occupation: a call to orthodoxy - Bevan, Chris (Sweet and Maxwell, 2016)
Those in actual occupation is one example of protection for an interest which although unregistered overrides a registered disposition and was first introduced by the notorious s70(1)(g) Land Registration Act 1925. Today the applicable law is provided for in Schedule 3, paragraph 2 of the Land Registration Act 2002 (hereafter the ‘2002 Act’). Long regarded as a ‘difficult concept to define in terms of its scope and meaning,’ actual occupation has been described as exuding an almost ‘enigmatic status.’ In part this may result from the fact that while the machinery of Schedule 3, paragraph 2 provides, in certain measure, parameters for the operation of the principle, it falls far short of stipulating a working definition of the concept nor does it offer a comprehensive statutory code or formula for when actual occupation will in fact arise. Whilst this delivers a guarantee of judicial flexibility, the corollary of this statutory lacuna has been piecemeal interpretation of the principle of actual occupation through incremental case law developments and judicial refinement as to the ‘elements’ that inform its operation. In 2003, the year in which the 2002 Act came into force, Dixon in this journal, asked whether ‘the substantive law reforms will produce unwelcome or unexpected effects because they are not located in an e-conveyancing system?’ Over a decade later, this article builds on this question, contending that we are indeed seeing these very unwelcome and unexpected effects as regards the operation of actual occupation. Drawing on a triptych of recent cases (Link Lending, Thompson v Foy, Thomas v Clydesdale ) and building on the work of Bogusz in the area, this article locates the emerging, expansive judicial approach to actual occupation in contemporary jurisprudence as demonstrated by court’s willingness to engage in a vastly more subjective assessment of the intentions, wishes and feelings of the parties in order to determine questions of actual occupation. This article argues strongly against this expansive approach and makes the case for a return to a more tightly-defined, less elastic, less subjective determination of actual occupation. It is argued that the current approach is both inconsistent with the fundamental aims of our land registration system and out-of-step with the historical trajectory of net-tightening and contraction in the scope of overriding interests in property law in England and Wales. The article begins by revisiting the motivations that provided the impetus for the 2002 Act and makes use of this enquiry as an essential backdrop for the subsequent analysis of the current judicial approach to actual occupation as evidenced in recent decisions of the court. In so doing, this article contends that the courts are failing to have due regard to the central tenet and impulse underpinning the 2002 Act’s reform agenda and the statutory language of Schedule 3. The article concludes by calling for a rejection of the current approach and for a return to orthodoxy engaging a more faithful and delimited rendering of actual occupation under the 2002 Act.